THE DIGITAL TRACE OF SOCIAL MEDIA ‘X’ IN FRAMING THE 2024 JAKARTA GOVERNOR CANDIDATES (RIDWAN KAMIL AND PRAMONO ANUNG) - Aura, Aldias Dayang Lara (Reflektika, 2025)
As the 2024 Jakarta Governor Election approaches, digital footprints are increasingly significant in shaping public perception. Candidates are judged based on their vision, mission, and past digital activities, including social media statements and posts. This phenomenon can be seen from the resurfacing of old posts from two candidates, Ridwan Kamil and Pramono Anung, which contained vulgar humour and later became the subject of public debate, especially on the platform X. Many users revisited and reposted old posts from two candidates, Ridwan Kamil and Pramono Anung. Many users revisited and condemned the old posts, intensifying the discussion in the public sphere. Although the posts were not initially related to political interests, they have now become a reference for evaluating the character and integrity of candidates. Certain groups seem to be engaged in strategic framing in this context, directing greater public attention towards specific candidates even though the issue involves many parties.